Policy Design for Research and Innovation Politics, Institutions and Interest Intermediation Practices - Acciai, Claudia (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
This book investigates the determinants of policy design choices in an area of public policy embracing multiple sectors of public responsibilities: Research and Innovation (R&I). Drawing on case studies from France and Italy, it assesses how governments design research and innovation policy strategies. It also examines how policymakers and stakeholders translate their interests into different design strategies, and the impact of varying political orientations and institutional setups on shaping choices for alternative policy instruments. Lastly, the book considers how the interactions between policy makers and policy takers influence policy design choices. It will appeal to scholars and students of comparative public policy, public administration, emerging technologies, and governance. Claudia Acciai is a researcher at the Department of Sociology, Copenhagen University, Denmark. Her research interests include comparative public policy analysis, publicadministration, innovation studies, and science of science.
1. An introduction to Research and Innovation Policy Design -- 2. The Determinants of Policy Design Choices: a Theoretical Framework for Analysis -- 3. Choosing and Blending Instruments for R&I Policies -- 4. Research and Innovation Policy Design in France -- 5. Research and Innovation Policy Design in Italy -- 5. Comparative Research and Innovation Policy Design.
Keywords: Political planning; Political science; Comparative government; Technological innovations; Public Policy; Governance and Government; Comparative Public Policy; Innovation and Technology Management